Rasionalitas Indonesia dalam Pengimplementasian â€œ40+9 Rekomendasiâ€ FATF - Puspapertiwi, Sheiffi (Universitas Muhammadiyah Yogyakarta, 2016)
Global anti-money laundering and countering the financing of terrorism (AML/CFT) regime set up by G7 countries in 1989 had established a nontreaty yet significantly influencing standard setter body named Financial Action Task Force (FATF). Regime norms codified by FATF in â€œ40+9 Recommendationsâ€, hand in hand with â€œNon-cooperative Countries and Territories (NCCTs)â€ list have become two most powerful instruments in enforcing international AML/CFT regime, not only for member but also non member countries, including Indonesia. This study is aimed to explore the reasons behind Indonesiaâ€™s decision to adopt and thus implement â€œ40+9 Recommendationsâ€. Using power-based regime approach and the economic sanction theory, this research finds that the said decision is a result of rational calculation, considering both international and domestic dynamics. On international side, there are global financial hegemon countries as FATF members behind â€œ40+9 Recommendationsâ€ who can act unilaterally to foster and enforce its global implementation. On the domestic side, its implementation can provide a basis for good financial governance, a much needed foundation to build anti-corruption and anti-terrorism national regime.